Discriminative-Stimulus Effects of Synthetic Cathinones in Squirrel Monkeys - Wakeford, Alison G P; Sherwood, Alexander M; Prisinzano, Thomas E; Bergman, Jack; Kohut, Stephen J; Paronis, Carol A (The international journal of neuropsychopharmacology, 2021)
Abstract Background Synthetic cathinones display overlapping behavioral effects with psychostimulants (e.g., methamphetamine [MA]) and/or entactogens (e.g., 3,4-methylenedioxymethaphetamine [MDMA])—presumably reflecting their dopaminergic and/or serotonergic activity. The discriminative stimulus effects of MDMA thought to be mediated by such activity have been well characterized in rodents but have not been fully examined in nonhuman primates. Methods The present studies were conducted to systematically evaluate the discriminative stimulus effects of 5 abused synthetic cathinones (methylenedioxypyrovalerone [MDPV], α-pyrrolidinovalerophenone [α-PVP], methcathinone [MCAT], mephedrone, and methylone) in adult male squirrel monkeys trained to distinguish intramuscular injections of MA (0.1 mg/kg; n = 4) or MDMA (0.6 mg/kg; n = 4) from vehicle. Results Each training drug produced dose-dependent effects and, at the highest dose, full substitution. MDMA produced predominantly vehicle-like responding in the MA-trained group, whereas the highest dose of MA (0.56 mg/kg) produced partial substitution (approximately 90% appropriate lever responding in one-half of the subjects) in the MDMA-trained group. MDPV, α-PVP, and MCAT produced full substitution in MA-trained subjects, but, at the same or higher doses, only substituted for MDMA in one-half of the subjects, consistent with primarily dopaminergically mediated interoceptive effects. In contrast, mephedrone and methylone fully substituted in MDMA-trained subjects but failed to fully substitute for the training drug in MA-trained subjects, suggesting a primary role for serotonergic actions in their interoceptive effects. Conclusions These findings suggest that differences in the interoceptive effects of synthetic cathinones in nonhuman primates reflect differing compositions of monoaminergic actions that also may mediate their subjective effects in humans.